Hierarchically structured TIO2 nanorod spheres for clean water and energy production - Bai, Hongwei (2014)
This study focuses on the synthesis of hierarchical TiO2 nanorod spheres for photocatalytic clean water and energy production. TiO2 nanorod spheres were firstly synthesized by developing a facile template-free low-temperature hydrothermal method. In order to overcome the drawbacks of hydrothermal method for practical engineering applications, facile novel calcination method was developed to scale-up fabricate TiO2 nanorod spheres via deliberately adding TiCl3 into resorcinol and formaldehyde reaction. Hydrothermally synthesized TiO2 nanorod spheres were applied for concurrent photocatalytic membrane filtration for water purification via a “win-win” strategy to maximize the advantages of photocatalysis and membrane filtration. Calcined TiO2 nanorod spheres were used for simultaneous photocatalytic H2 generation and Cu2+ recovery. The formation mechanisms of TiO2 nanorod spheres were elaborated and the detailed influencing factors were investigated systematically. It is of great significance not only in promoting the scale-up fabrication of hierarchical TiO2 nanorod spheres but also in broadening their applications in clean water and energy production.